1986
DOI: 10.1128/mcb.6.12.4221
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase inhibitors can selectively interfere with different stages of simian virus 40 DNA replication.

Abstract: I have found that antineoplastic drugs which are known to be inhibitors of mammalian DNA topoisomerases have pronounced and selective effects on simian virus 40 DNA replication. Ellipticine, 4'-(9-acridinylamino)methanesulfon-m-aniside, and Adriamycin blocked decatenation of newly replicated simian virus 40 daughter chromosomes in vivo. The arrested decatenation intermediates produced by these drugs contained single-strand DNA breaks. Ellipticine in particular produced these catenated dimers rapidly and effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
86
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 16 publications
2
86
0
Order By: Relevance
“…The role of topoisomerases in DNA replication has been studied in a number of organisms (Maxwell & Geltert, 1985;Wang, 1985). In the case of viruses, Snapka (1986) has reported that topoisomerase II inhibitors including ellipticine block decatenation of newly replicated simian virus 40 daughter chromosomes and lead to an accumulation of catenated dimers containing single-strand DNA breaks and that camptothecin rapidly breaks the replication fork in growing Cairns structures. Recent reports have shown that the cellular topoisomerase II can induce double-strand breaks at specific locations in herpes simplex virus type 1 DNA and is involved in aspects of viral replication at late times in the infection cycle (Ebert et aL, 1990).…”
Section: Topoisomerase I and Ii Activities Are Required For Epstein-bmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of topoisomerases in DNA replication has been studied in a number of organisms (Maxwell & Geltert, 1985;Wang, 1985). In the case of viruses, Snapka (1986) has reported that topoisomerase II inhibitors including ellipticine block decatenation of newly replicated simian virus 40 daughter chromosomes and lead to an accumulation of catenated dimers containing single-strand DNA breaks and that camptothecin rapidly breaks the replication fork in growing Cairns structures. Recent reports have shown that the cellular topoisomerase II can induce double-strand breaks at specific locations in herpes simplex virus type 1 DNA and is involved in aspects of viral replication at late times in the infection cycle (Ebert et aL, 1990).…”
Section: Topoisomerase I and Ii Activities Are Required For Epstein-bmentioning
confidence: 99%
“…In the case of animal viruses, topoisomerases play important roles in viral DNA replication, transcription, packaging and integration (Foglesong & Bauer, 1984;Snapka, 1986;Nishiyama et al, 1987;Benson & Huang, 1988;Champoux, 1988; Richter & Strausfeld, 1988;Ebert et al, 1990;Priel et al, 1990Priel et al, , 1991 Schaack et al, 1990a, b;Wong & Hsu, 1990;Yamada et al, 1990;Gu & Rhode, 1991;Priel et al, 1991 ;Wang & Rogler, 1991). Topoisomerase I changes the linking numbers of topological DNA domains in integral steps of one by introducing transient singlestrand breaks.…”
mentioning
confidence: 99%
“…The virus replicates in the infected cell nucleus forming structures very similar to eukaryotic chromatin (minichromosomes) (Griffeth et el., 1975;Tooze et et., 1980). In vitro studies have suggested that topoisomerase I and II enzymes are important for the replication of SV40 (Yang et aI., 1987;Snapka, 1986). Topoisomerase I acts during elongation to relax the positive supercoils which are generated as the parental DNA unwinds.…”
Section: Introductionmentioning
confidence: 99%
“…The genomes of most DNA viruses and retroviruses are detectable in the nuclei as eDNA during at least a portion of the viral life cycle (Fields et al 1996). Infected cells often contain complex patterns of different size viral eDNAs which reflect various stages in replication of the viral genome (Snapka 1987, Cotmore & Tattersall 1998. These patterns are produced by pauses in replication which result in the accumulation of discrete size fractions of DNA rather than simply a continuum of sizes of elongating DNA (Snapka 1987).…”
mentioning
confidence: 99%
“…Infected cells often contain complex patterns of different size viral eDNAs which reflect various stages in replication of the viral genome (Snapka 1987, Cotmore & Tattersall 1998. These patterns are produced by pauses in replication which result in the accumulation of discrete size fractions of DNA rather than simply a continuum of sizes of elongating DNA (Snapka 1987). In addition to extrachromosomal forms, some DNA viruses and all retroviruses also exhibit integrated stages where one or more viral genomes are integrated into chromosomal DNA.…”
mentioning
confidence: 99%